A review of common influencing factors and possible mechanisms associated with allergic diseases complicating tic disorders in children - Zhang, Panpan; Zheng, Zhimin; Sun, Hao; Gao, Tieying; Xiao, Xuwu (Frontiers in Pediatrics, 2024)
Over the past few decades, the incidence of childhood allergic diseases has increased globally, and their impact on the affected child extends beyond the allergy itself. There is evidence of an association between childhood allergic diseases and the development of neurological disorders. Several studies have shown a correlation between allergic diseases and tic disorders (TD), and allergic diseases may be an important risk factor for TD. Possible factors influencing the development of these disorders include neurotransmitter imbalance, maternal anxiety or depression, gut microbial disorders, sleep disturbances, maternal allergic status, exposure to tobacco, and environmental factors. Moreover, gut microbial disturbances, altered immunological profiles, and DNA methylation in patients with allergic diseases may be potential mechanisms contributing to the development of TD. An in-depth investigation of the relationship between allergic diseases and TD in children will be important for preventing and treating TD.